Revision of Silhouettanus with description of nine new species (Hemiptera: Heteroptera: Schizopteridae) - Hill, Lionel (Zootaxa, 2014)
The description of Silhouettanus alboclavatus Emsley, 1969 (Hemiptera: Schizopteridae) is recognized, supplemented and nine new species of Silhouettanus Emsley, 1969 (Hemiptera: Schizopteridae) are described from Queensland and New Caledonia. They are S. bamaganus sp. n., S. insulomagnus sp. n., S. insuloparvus sp. n., S. lintrarius sp. n., S. magnus sp. n., S. monteithi sp. n., S. pilosus sp. n., S. tinnulus sp. n. and S. turbator sp. n. A key to males of the species is provided. Notes on two undescribed Australian genera also with porrect heads and the holotype of Dictyonannus flavus Gross, 1951 are given. Morphological comparisons with other schizopterid genera are given.